The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1093/jcr/ucab044
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Ideology

Abstract: Ideology plays a central role in consumer decisions, actions, and practices. While there have been numerous studies of ideological formations in specific consumption contexts, an integrative theoretical framework on consumption ideology has been missing. The theoretical framework presented in this article integrates systemic, social group, and social reality perspectives from social theory with prior consumer research to conceptualize consumption ideology as ideas and ideals that are related to consumerism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 100 publications
0
23
0
6
Order By: Relevance
“…At the theoretical level, this study is the first to explore the psychological and contextual mechanisms contributing to the formation of locavorism as a proper form of consumer ideology. In light of the prominent role of consumer ideologies in shaping consumer attitudes, behaviours and practices (Schmitt et al, 2021), our study identified three main sources of influence. In particular, locavorism formation is shaped through individual and social influences and exogenous factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the theoretical level, this study is the first to explore the psychological and contextual mechanisms contributing to the formation of locavorism as a proper form of consumer ideology. In light of the prominent role of consumer ideologies in shaping consumer attitudes, behaviours and practices (Schmitt et al, 2021), our study identified three main sources of influence. In particular, locavorism formation is shaped through individual and social influences and exogenous factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the food consumption literature, consumer ideologies typically assume the form of action-oriented ideas shared among a group of individuals that provide values, meaning and identity (Schmitt et al, 2021). Ideology formation is iterative in nature, as social practices continuously evolve in new forms of ideology.…”
Section: Introductionmentioning
confidence: 99%
“…The tensions between micro and macro, mine, and yours, public and private, fair, and unfair, rights and wrongs became stronger, prompting adaptation and resignification of many consumption practices. Consumption ideologies -ideas and ideals manifested in consumers' social representations and communicated in their actions in marketplaces -thus have a meaningful role here (Schmitt, Brakus, & Biraglia, 2021). In the case of working from home, for example, the use of video-streaming platforms, such as Zoom, have transformed our private living rooms, bedrooms, kitchens, and any available space in the house into shared public spaces.…”
Section: Introductionmentioning
confidence: 99%
“…We can now buy virtual clothing to go with our virtual presence on meeting apps. And many of us, for better or for worse, transform our rooms with Zoom backgrounds that may work as a symbolic escape route to personal dreams (e.g., a beach in Rio de Janeiro) or simply to mask the real-life chaos behind the screen (Schmitt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Agora é possível comprar roupas virtuais para nossa presença virtual em aplicativos de reunião. Muitos de nós, para o bem ou para o mal, transformam seus quartos com fundos Zoom que podem funcionar como uma rota de fuga simbólica para sonhos pessoais (por exemplo, uma praia no Rio de Janeiro) ou simplesmente para mascarar o caos da vida real por trás da tela (Schmitt et al, 2021). Dois anos após o início da pandemia, as pessoas ainda estão involuntariamente fazendo malabarismos entre aqui e ali, na esperança de encontrar significados antigos e novos em suas atividades cotidianas.…”
unclassified